2012
DOI: 10.1155/2012/346286
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Management of Biliary Complications following Liver Transplantation after Donation from Cardiac Death Donors

Abstract: There was a trend toward increasing incidence of total biliary complications in recipients of DCD liver allografts compared with those receiving DBD livers, and the rate of diffuse ischemic cholangiopathy was significantly higher. Focal ischemic type biliary strictures can be treated effectively in DCD liver transplant recipients with favourable results. Diffuse ischemic type biliary strictures in DCD liver transplant recipients ultimately requires retransplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…An 'ischemic cholangiopathy' evolves in >20% of recipients (79). The clinical picture is similar to NAS of other etiology, but it manifests regularly within 3 months after LT (78). Its clinical course is often more severe and retransplantation required in a significant percentage (79,80).…”
Section: Special Issues Of Dcdmentioning
confidence: 96%
See 1 more Smart Citation
“…An 'ischemic cholangiopathy' evolves in >20% of recipients (79). The clinical picture is similar to NAS of other etiology, but it manifests regularly within 3 months after LT (78). Its clinical course is often more severe and retransplantation required in a significant percentage (79,80).…”
Section: Special Issues Of Dcdmentioning
confidence: 96%
“…During the additional period of WIT without organ preservation stasis and thrombus formation in small vessels is expedited (77). Since also the peribiliary plexus is involved, the incidence of biliary complications is almost doubled (78). An 'ischemic cholangiopathy' evolves in >20% of recipients (79).…”
Section: Special Issues Of Dcdmentioning
confidence: 99%
“…24 Additionally, many single-center studies ( Table 2) have suggested that both graft function and patient survival are comparable between DCD and DBD liver transplants. [25][26][27][28][29] Meurisse and associates reported DCD liver transplants had 1, 3, and 5-year graft survival rates of 90%, 82%, and 82% and patient survival rates of 93%, 85%, and 85%, which were similar to DBD liver transplant survival rates of 85%, 74%, and 68% (P = .524) and patient survival rates of 88%, 78%, and 72% (P = .348). 25 Grewal and associates were able to achieve comparable longterm outcomes between DCD and DBD liver transplants with 1-, 3-, and 5-year patient and graft survival rates for DCD transplants (91.5%, 88.1%, and 88.1% and 79.3%, 74.5%, and 71.0%) vs DBD transplants (87.3%, 81.1%, and 77.2% and 81.6%, 74.7%, and 69.1%).…”
Section: Discussionmentioning
confidence: 71%
“…20,25,26,44 A single-center study showed an overall biliary complication rate of 50% for DCDs versus 28.3% for DBDs (P = .012) with biliary stricture rates of 46.7% and 26.5% (P = .018). 25 Croome and associates reported that 25% of DCD liver transplants developed biliary complications compared with 13% of DBD liver transplants (P = .062).…”
Section: Emre a Eren Et Al/experimental And Clinical Transplantationmentioning
confidence: 99%
See 1 more Smart Citation